The Challenges Faced by Hemodialysis Patients in Maintaining Quality of Life: A Scoping Review - A. M. Albatta, Rana; Fitri Arofiati (LPPM Universitas Prima Nusantara Bukittinggi, 2026)
Background: Chronic kidney disease (CKD) affects 9.1% of the global population and is a major cause of mortality. Hemodialysis, the primary treatment for end-stage renal disease (ESRD), sustains survival but creates significant psychological, physical, social, and clinical challenges that reduce quality of life. Methods: This scoping review followed Arksey and O’Malley’s framework, Joanna Briggs Institute (JBI) methodology, and PRISMA-ScR guidelines. Six databases: Scopus, Sage, PubMed, Springer, Emerald and ScienceDirect from the period of 2019 to 2024 were searched for studies on adult hemodialysis patients addressing quality of life. Ten studies met the inclusion criteria and were charted and thematically analyzed. Results: The studies (n = 10) were conducted in Asia, the Middle East, and South America, with 12–271 participants. Four challenge domains were identified: (1) psychological challenges; depression and anxiety were the most frequent predictors of poor quality of life; (2) physical challenges; fatigue, pain, anemia, and dialysis-related complications limited daily functioning and work; (3) social challenges; isolation, stigma, and caregiver burden reduced participation; and (4) clinical challenges; comorbidities, infections, and adherence issues further worsened outcomes. Conclusion: Hemodialysis patients face complex, overlapping burdens. Multidisciplinary interventions that integrate psychological care, symptom control, social support, and stigma reduction are needed. Future research should use longitudinal and interventional approaches to improve long-term patient outcomes.